The impact of work hours on work‐to‐family enrichment and conflict through energy processes: A meta‐analysis. (9th January 2022) - Pak, Sunjin; Kramer, Amit; Lee, Yin; Kim, Ki‐Jung
Summary: We use a meta‐analysis to introduce a framework that integrates research on the relationship between working hours and the work–family interface. Using the work–home resources model, we integrate work–family enrichment and conflict theory, focusing on the positive and negative mediational processes of human energy. We conceptualize working hours, within the framework of the work–home resources model, as the potential to increase vigor and exhaustion in tandem, which, in turn, would lead to increased work–family enrichment and work–family conflict, respectively. Our model suggests, and a meta‐analytic investigation ( N = 459 846), supports that the two dimensions of human energy, vigor and exhaustion, mediate the relationship between working hours and work‐to‐family enrichment and conflict, respectively. Taken together, our findings contribute to the literature by integrating the positive and negative energy mechanisms in the relationship between working hours and work‐to‐family enrichment and conflict. Specifically, by showing the parallel paths of vigor and exhaustion that occur when individuals increase working hours, we reconcile mixed findings regarding the effect of working hours on the work–family interface.